An empirical validation of instructional materials on methods of improving water potability - Alturas, Gerarda Sale 1947- (1978)
This study developed and validated supplementary instructional materials on methods of improving water potability for use in the first and second year high school classes. The first lesson included physical, biological, and bacteriological examination of the local water supply. The second lesson suggested activities on the physical and chemical methods of water treatment. To test the practicability, the instructional materials were tried out on a representative sample composed of 48 first and second year students of 2 high schools in Batangas City: Banaba West Barrio High School and Saint Bridgette's College. On the basis of the findings, it was concluded that the instructional materials are workable and appropriate for the first and second year high school students.